Histopathological changes in dilated ascending aorta associated with aortic valve cuspidity - Karalko, Mikita; Stejskal, Vaclav; Dergel, Martin; Gofus, Jan; Timbilla, Salifu; Zaloudkova, Lenka; Zacek, Pavel; Pojar, Marek; Vojacek, Jan (European journal of cardio-thoracic surgery, 2021)
OBJECTIVES: Patients with a bicuspid aortic valve (BAV) often present with a dilated ascending aorta. However, the underlying pathogenesis for the observed changes in the aortic wall and the resulting aneurysmal dilation remains a subject of debate. This study aims to compare the histological abnormalities of the ascending aorta in BAV and tricuspid aortic valve (TAV) patients and their correlation with aortic diameter and patient age. METHODS: A total of 376 patients from our institution's clinical database were included in the retrospective analysis. These patients underwent either elective surgery for ascending aorta dilation or emergency surgery for aortic dissection, either isolated or with a structurally diseased aortic valve. After excision, the ascending aorta samples were analysed by a pathologist. RESULTS: On histological examination, a higher degree of elastic fibre fragmentation and loss and mucoid extracellular matrix accumulation was present in the samples from TAV patients when compared with that from BAV patients (P < 0.001). However, correlation was poor for all variables when considering aortic diameter and histological abnormalities or age and histological abnormalities in both BAV and TAV patients. CONCLUSIONS: Our study demonstrates a greater incidence of severe histological abnormalities in TAV patients when compared with BAV patients.
Keywords: Aorta; Retrospective Studies; Heart Valve Diseases; Medial degeneration; retrospektivní studie; dilatace patologická; Bicuspid aortic valve; aorta; nemoci srdečních chlopní; Ascending aorta dilation; Aortic Valve; aortální chlopeň; Humans; lidé; Aortopathy; Dilatation, Pathologic